Optimal Decisions of a Green Supply Chain under the Joint Action of Fairness Preference and Subsidy to the Manufacturer - Zi-yuan Zhang; Duan-xiang Fu; Qing Zhou (Discrete Dynamics in Nature and Society)
Government subsidy promotes the development of green supply chain, and the influence of decision-makers’ behavioral preferences becomes increasingly prominent in green supply chain management. In order to further enrich the research content of green supply chain, we first use Stackelberg game theory to construct game models by taking the product green degree, wholesale price and retail price as the decision variables, then we work out the equilibrium strategies of the manufacturer and the retailer under four decision scenarios, and reveal the impact differences between the two parties’ fairness preference behaviors. Our research mainly has the following findings: Firstly, the government subsidy to the manufacturer can benefit these two parties and can have certain impact on the optimal decisions only by working with the green product market expansion efficiency. Secondly, these two parties’ fairness preference behaviors can cause serious damage to the other party’s profit and the overall profit of green supply chain, and increase the rate of their own profit in the overall profit of green supply chain, but the difference is that the retailer’s fairness preference behavior can cause a greater decline in product green degree and wholesale price, and when certain conditions are met, its own profit may rise compared to its fairness neutral, while the manufacturer’s fairness preference behavior can cause a greater damage to the overall profit of green supply chainand make its own profit always be lower than its fairness neutral. Thirdly, the government subsidy to the manufacturer and the fairness preference behaviors of both parties can cause a stack effect on the optimal solutions, which means that the subsidy government provides for the manufacturer can aggravate the negative influence caused by these two parties’ fairness preference behaviors.